Analisis Perkembangan Kecerdasan Visual Spasial Anak Usia Dini Kelompok B di RA Rahmatullah - Fauziah Nasution; Nur Sa’adah; Ijar Salna; Alya Sabrina Ramdhani Hsb (Inovasi Pendidikan dan Anak Usia Dini, 2025)
The purpose of this study was to find out about the early observation of visual-spatial intelligence at RA Rahmatullah Tanjung Morawa. The results of the observation were seen during security activities, children were involved in drawing activities freely. From here, it can be observed that some children have shown good development in visual spatial intelligence. This can be seen from their ability to draw objects around them and combine colors to create images that match their vision. This study aims to explain the results of the study on the development of children's visual spatial intelligence. The type of research adopted in this study is qualitative research. The method chosen in this study is qualitative with a type of phenomenological research, which is intended to explore the phenomena that occur in the school environment to provide the information needed. From the results of the study obtained through observation and interviews with class teachers of group B at RA Rahmatullah Tanjung Morawa, it can be seen that the development of children's visual spatial intelligence in group B has developed well. The intelligence possessed by children is shown by their ability to perceive the visual world, namely the ability to capture and mix colors when coloring, their pleasure in drawing and doodling, imagining, making simple designs, and the ability to understand direction and shape, and also in creating various shapes.